Understanding social inequality - Butler, Tim 1949- (Sage, 2007)
This title brings the study of social stratification and inequality into the 21st century. Starting with the widely agreed 'fact' that the world is becoming more unequal, it brings together sociological and geographical issues that show how place has become an important focus for understanding new trends in social inequality
Literaturangaben und Index
Neue Seitenzählung in jedem Kapitel, abweichend von Seitenzählung in print-Version
Keywords: Social stratification; Equality; Soziale Schichtung; Soziale Ungleichheit